Pengaruh Tunjangan Tambahan dan Remunerasi terhadap Kinerja Pegawai dengan Keterlibatan Pegawai Sebagai Variabel Mediasi (Studi Pada Pengadilan Tinggi Jawa Tengah) - Arta, Yohanes Primada Dwi; Tjahjaningsih, Endang (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this research is to examine and analyze the effect of additional benefits and remuneration on employee engagement. This study aims to examine and analyze how employee engagement mediates the effect of additional benefits and remuneration on employee performance. The population of this study is 79 employees, from staff to management, representing all employees of the Central Java High Court. Primary data was collected using a questionnaire. Multiple linear regression was used as the data analysis method. The results show that additional benefits influence employee engagement, remuneration influences employee engagement, additional benefits influence employee performance, remuneration influences employee performance, employee engagement influences employee performance, and employee engagement mediates the effect of additional benefits on employee performance at the Central Java High Court. Therefore, employee engagement can increase employee potential, with high additional benefits improving employee performance, and employee engagement mediates the effect of remuneration on employee performance at the Central Java High Court. Therefore, employee engagement can improve employee performance through high and expected remuneration.